RISK MANAGEMENT OF SEAWEED CULTIVATION BUSINESS - Rahma Puspitasari; Fuad Hasan (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Seaweed production in Bluto District has fluctuated from time to time. This indicates a production risk and has an impact on farmers’ income. The purpose of this research is to find out factors causing the risk of seaweed production and to find out the strategies used to reduce the risk of seaweed production in Bluto District, Sumenep Regency. Primary data were collected from 50 farmers who were selected by the census. Data were analyzed using Failure Mode of Effect Analysis (FMEA) and descriptive analysis to see ex-ante, interactive, and ex-post strategies. The results of the analysis showed that the risk factors for seaweed production above the critical value were weather, wave conditions, and pests and diseases. The risk factors below the critical value were water quality, floating raft conditions, seedling quality, and polluted environment. The risk management strategy carried out was to check and control the tools and seeds to be used, and to accelerate the harvest period when the weather was not supportive.